Playing With Fire: Proinflammatory Virulence Mechanisms of Group A Streptococcus - Wilde, Shyra; Johnson, Anders F.; LaRock, Christopher N. (Frontiers in Cellular and Infection Microbiology, 2021)
Group A Streptococcus is an obligate human pathogen that is a major cause of infectious morbidity and mortality. It has a natural tropism for the oropharynx and skin, where it causes infections with excessive inflammation due to its expression of proinflammatory toxins and other virulence factors. Inflammation directly contributes to the severity of invasive infections, toxic shock syndrome, and the induction of severe post-infection autoimmune disease caused by autoreactive antibodies. This review discusses what is known about how the virulence factors of Group A Streptococcus induce inflammation and how this inflammation can promote disease. Understanding of streptococcal pathogenesis and the role of hyper-immune activation during infection may provide new therapeutic targets to treat the often-fatal outcome of severe disease.